Spontaneous goal versus spontaneous trait inferences: How ideology shapes attributions and explanations. (12th September 2019) - Olcaysoy Okten, Irmak; Moskowitz, Gordon B.
Abstract: Past research documented liberals' greater tendency than conservatives to take situational determinants of others' actions into account when forming causal attributions, and conservatives' greater tendency to seek consistency. We hypothesize that liberals (vs. conservatives) should be more likely to make spontaneous goal inferences (SGIs). Conservatives, however, should tend to implicitly infer invariant rather than variant characteristics from others' behaviors, drawing spontaneous trait inferences (STIs) rather than SGIs. Experiment 1 and 2 supported those hypotheses by illustrating differences in the type of implicit inferences formed by liberals and conservatives in a false recognition paradigm common to the STI literature. Experiment 3 revealed similar differences in conservatives' and liberals' goal and trait inferences when making open‐ended causal explanations for others' actions.